Developing Thai Undergraduate Online Digital Citizenship Skills (DCS) Under the New Normal - Prarichart Ruenphongphun; Aukkapong Sukkamart; Paitoon Pimdee (Journal of Higher Education Theory and Practice, 2022)
The study aims to develop a model and assess the suitability of a digital citizenship skills (DCS) model for online teaching and learning for Thai undergraduate students. In-depth interviews and content analysis from seven Thai academic experts in 2020 were used for the analysis. The experts’ questionnaires suitability was analyzed using propriety standards, utility standards, feasibility standards, and accuracy standards as outlined by the Joint Committee on Standards for Educational Evaluation (JCSEE). After that, descriptive statistics including the mean and standard deviation (SD) were used to assess the results from the five-level agreement scale used. The final DCS model consisted of five components. These included the learner (L), the instructors (I), the Internet, intranet, and extranet network components (I), the platform component for online teaching, and information and communication technology (ICT) enabled devices (P), and personalized learning (P) (LIIPP Model). Overall model suitability according to the experts’ input was judged to be at a very high level (mean = 4.61, SD = .51).
Keywords: Technology-Enhanced Education Studies